Analisis Rasio Solvabilitas dalam Mengukur Kinerja Keuangan PT Kimia Farma (Persero) Tbk (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze solvency rations in measuring the financial performance of PT Kimia Farma (Persero) Tbk. The solvency ratos examined include the Debt to equity ratio (DER) and Debt to asset ratio (DAR). The main focus of this research is to assets the extent to which the company is capable of fulfilling its long-term obligations using its own capital and total assets. The research uses quantitative data derived from the company’s annual financial statements from 2019 to 2023. A desriptve approach is employed, using financial ratio analysis as the primary tool to evaluate the company’s solvency level over the study period. The result of the analysis indicate that both Debt to equity ratio and Debt to asset ratio of PT Kimia Farma (Persero) Tbk consistenly exceeded industry standars during the period under review. The high valuew of DER and DAR suggest that the company relies heavily on external financing through debt. This the dependency has led to a high financial burden with increasing obligations that the company must cover each year. So overall it shows that the financial condition of PT Kimia Farma (Persero) Tbk in terms of solvency ratio is in the unhealthy category. The company has not yet demonstrated an optimal and sustainable ability to cover its long-term liabilities, highlighting the need for improved financial strategies to balance its capital structure in the future.